The Effect of Work Environment and Work Discipline on Employee Performance at PT. X - Ovi Levia Arista Ovi; Agung Wahyu Handaru; Sholikhah (LPPM Universitas Negeri Jakarta, 2022)
Abstract The purpose of this study was to determine the effect of the Work Environment and Work Discipline on Employee Performance at PT. X. The subject of this research is PT. X, a company engaged in housing construction located in Bogor. The population of this study was 101 people, and the sampling method used was saturated sampling, so the number of samples in this study was also 101 people. This research uses multiple linear regression analysis method in analyzing the research data. The results showed that the work environment and work discipline had a significant positive effect on employee performance, either partially or simultaneously.Keywords: Work Environment, Work Discipline, Employee Performance